GERAKAN LITERASI SEKOLAH SEBAGAI STRATEGI PENINGKATAN MINAT BACA SISWA DI SEKOLAH DASAR - Audini Yanwar, Hilma; Neni Nadiroti Muslihah; De Budi Irwan Taofik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading is an important activity in expanding students' knowledge and insight. The success of reading activities is influenced by reading interest, namely the internal drive that makes individuals interested in reading. Low reading interest can hinder students' ability to keep up with the development of constantly changing information. This study aims to describe the implementation of the School Literacy Movement (GLS) as a strategy to increase reading interest in elementary school students. The research approach uses a descriptive qualitative method with a purposive sampling technique. The research subjects consisted of 25 fifth-grade students who actively participated in the GLS program. Data were collected through observation, interviews, and documentation. The results showed that the habituation stage in GLS, especially the fifteen-minute reading activity before learning, was effective in fostering reading interest. Silent reading activities were the most conducive form of activity in building literacy habits and student engagement.